Sensitivity of [11C]ORM-13070 to increased extracellular noradrenaline in the CNS – a PET study in human subjects - Lehto, Jussi; Johansson, Jarkko; Vuorilehto, Lauri; Luoto, Pauliina; Arponen, Eveliina; Scheinin, Harry; Rouru, Juha; Scheinin, Mika (Psychopharmacology, 2015)
Rationale No validated methods have been available for studying brain noradrenergic neurotransmission in vivo in humans. Positron emission tomography (PET) radiotracers are widely used in clinical drug development targeted to brain receptors and can also in some cases be employed to monitor extracellular (synaptic) neurotransmitter concentrations. Objectives The objective of this study is to test the sensitivity of [ 11 C]ORM-13070 uptake to increased concentrations of extracellular (synaptic) noradrenaline in the human brain. Methods Eight subjects underwent a control PET scan with [ 11 C]ORM-13070, a subtype-selective α 2C -adrenoceptor antagonist radioligand, and two PET scans after two different noradrenaline challenges, i.e. during ketamine infusion and after a dose of atomoxetine combined with cold stimulation. Tracer uptake in the caudate nucleus and putamen was described with AUC values in scan time windows of 10–20 and 5–30 min post injection and quantified with the ratio method. Voxel-based analysis was performed with average bound per free (B/F) ratio images. Results Both noradrenaline challenges were consistently associated with 10–20 % ( p < 0.05) reductions in tracer uptake in the dorsal striatum, as determined with region-of-interest-based analysis. Voxel-based analysis revealed significant reductions in B/F ratios in the dorsal striatum, in the brain stem and in several cortical areas. Reductions of 24 and 23 % were detected in the peak putamen clusters with ketamine and atomoxetine + cold, respectively. Conclusion Direct experimental support was gained for the suitability of [ 11 C]ORM-13070 for imaging of brain noradrenergic neurotransmission.